GHOSTS OF AN EMPIRE: BRITISH LEGACIES IN ASIA - Michael Share (Международная аналитика, 2018)
One hundred years ago, the British Empire controlled a quarter of the world’s area and population. Today only a dozen tiny islands remain of this once great empire. However, the British left a huge and permanent legacy behind in terms of the English language, a rule of law, banking, Protestantism, team sports, and parliamentary institutions. While some historians, notably Niall Ferguson, hold that the British legacy was a positive one, most historians believe the legacy was a negative one. Instead of being liberal and democratic, the British Empire was anti-democratic. Instead of fostering free trade, the Empire was protectionist toward the outside world. Notions of class and hierarchy were crucial. This article examines the British legacy in two former colonies in Asia--one huge and one tiny: India and Hong Kong. While in Hong Kong, Britain’s legacy has been fairly positive, in India it is quite negative. The British Empire was not a prelude to a modern 21st century Western world of democracy, multiculturalism, and liberal economics. The British Empire was something different– snobbery, hierarchy, and individualism, and must be understood on its own terms.